2020
DOI: 10.1007/s40820-020-00464-8
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and Challenges in Twisted Bilayer Graphene: A Review

Abstract: HIGHLIGHTS • This article presents an overview of twisted bilayer graphene (tBLG) on their fabrication techniques and twisting angle-dependent properties. • The properties of tBLG can be controlled by controlling the twisting angle between two graphene sheets. ABSTRACT Two-dimensional (2D) materials exhibit enhanced physical, chemical, electronic, and optical properties when compared to those of bulk materials. Graphene demands significant attention due to its superior physical and electronic characteristics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(62 citation statements)
references
References 146 publications
(210 reference statements)
0
58
0
Order By: Relevance
“…S7 and S8 †). 50 The intramolecular spacing between the consensus planes of the pyrene groups is 351.64 (15) pm, and these planes have bending angles 30 of just 3.8(4) . The pyrene groups are offset by only $50 pm from perfectly eclipsed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S7 and S8 †). 50 The intramolecular spacing between the consensus planes of the pyrene groups is 351.64 (15) pm, and these planes have bending angles 30 of just 3.8(4) . The pyrene groups are offset by only $50 pm from perfectly eclipsed.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12][13] Superconductivity arises in a duplex of two graphene sheets if one is twisted by a "magic angle" ($1.1 ) with respect to the other. 14,15 These uncommon electronic properties arise because atoms at interfaces have been arranged in precise congurations that are challenging to achieve.…”
Section: Introductionmentioning
confidence: 99%
“…This fact leaves the fine electronic structure of magic-angle TBG [1][2] unexplored, despite many theoretical speculations on the origin of the related exotic phenomena (for a review, see ref. [11]).…”
Section: Doi: 101002/adma202007503mentioning
confidence: 99%
“…In short, great progress on tBLG has been achieved by numerous excellent studies in recent years. Although a few reviews on its physical properties have been reported, [35][36][37] the systematical introduction and summary for the fabrication challenges and preparation strategies of tBLG, characterization methods of twist angle, and their unique physicochemical properties is still lacking. Herein, we describe the cutting-edge preparation methods of tBLG and analyze their features and drawbacks to disclose the influence in properties and application of tBLG.…”
Section: Introductionmentioning
confidence: 99%